INNOVATIVE ADAPTATION AND OPERATIONAL EFFICIENCY ON SUSTAINABLE COMPETITIVE ADVANTAGE OF FOOD AND BEVERAGE FIRMS IN KENYA. Issue 2 (2014) - Mutunga, Stephen Laititi; Minja, David; Gachanja, Paul
No abstract available